RISK â BASED AUDIT ATAS PENJUALAN (Studi Kasus Pada PT. UNITED MOTORS CENTRE) - Kumalasari, Intan Asri; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Sales are one of the existing factors which can generate profit in business; when the sale of goods is high, it will gain more profit obtains and the risk that might occur will be high as well. The establishment of audit on sales is expected to find out the information which free from fraud, so that it will increase efficiency and effectiveness of the sales of the company and the objective of the company can be achieved. This research is meant to develop the risk based audit method on sales at PT. United Motors Centre. With the risk based audit, when the risk is high and the attention that has to be given is getting great in order to ensure that the risk adequacy on a company can be managed in accord with the risk limit that has been determined by the company. This research is field study method and the technique applies observation, interview, and inspection. The result of this research shows that source of the risk is in the weak bond of a system and procedures (process, human resources, or internal control), environment and ways of working not conducive moreover some policies of the company are consider to be loose in dealing with the problems, and it has the potency to influence the security of the firm assets, statement reliability, and information that is related to financial, and functional efficiency and effectiveness in using the company resources.Keywords: Risk-based Audit, Sales, Risk Sources, Risk Potency.